Maintaining Balance: A Comprehensive Look of The Struggle Between Government Protection and Government Overreach in Regard to Mergers and Their Remedies - Bateman, Severine (American Journal of Trade and Policy, 2021)
In September of 2020, the Department of Justice made a change to the Merger Remedies Manual, which discusses the correct remedies for mergers that violate the standards in the Heart-Scott-Rodino Act and how to best enforce them. A deeper look at this manual prompts a deeper analysis on current antitrust merger standards and how they balance government power and personal liberties. The Merger Remedies manual and its corresponding document with the Federal Trade Commission, as well as the merger standards in regard to the rise of Private Equity Buyers and Big Tech, promote concern over the balance between constitutional rights and promoting fairness in the marketplace. This article is among the first to analyze how current merger remedies stand in being effective in regard to the technology sector, while also analyzing the constitutionality of those merger regulations.The article contributes to the literature in three primary ways. First, the article deeply analyzes the two manuals for merger remedies from the above mentioned agencies and determines which better balances governmental powers with personal liberties and where both agencies could improve. Second, the article outlines the current concerns with large technology companies and their current rights in regard to merger standards while also acknowledging their monopolizing tendencies, presenting ways in which such issues could more easily and constitutionally be regulated through antitrust merger laws. Third, the article analyzes the current stance from the merger regulating agencies towards private equity firms and how their changing stances and opinions support a less government-regulative stance towards private equity firm involvement.
Keywords: mergers; remedy; antitrust; business constitution; facebook; amazon; big tech; government